223 Challenging ACL reconstructed athletes and their sensorimotor system at return-to-sport: a vital step towards exposing the roots of their neuromuscular deficits. (3rd March 2020) - Smeets, Annemie; Verschueren, Sabine; Staes, Filip; Claes, Steven; Vandenneucker, Hilde; Vanrenterghem, Jos
Abstract : Background: Evidence increasingly suggests that neuromuscular alterations in ACL reconstructed (ACLR) patients are rooted in neurocognitive and proprioceptive deficits. Objective: The aim of this study was to reveal how neurocognitive and proprioceptive deficits determine neuromuscular control alterations seen in ACLR athletes. Design: Cross-sectional study. Setting: Athletes who return to a cutting or pivoting sport after an ACL reconstruction. Patients: 20 athletes who had an ACL reconstruction and were cleared by the surgeon/physiotherapist to return to sport (RTS), were tested at time of RTS. A control group of 20 uninjured athletes, matched for gender and type of sport, was included. Assessment of risk factors: All participants performed a stepping-down task under 4 conditions: 1. no additional challenges (NORM), 2. whilst performing a cognitive dual-task (DUAL), 3. whilst undergoing unpredictable surface perturbations (PERT), 4. whilst performing a cognitive dual-task + undergoing unpredictable surface perturbations. Main outcome measurements: Muscle activations of the vastus medialis (VM), vastus lateralis, hamstrings medialis (HM), hamstrings lateralis were recorded with surface EMG. Integrals were calculated over the landing period (50–250 ms after initial contact) and normalized to maximal voluntary contractions. Results: The ACLR athletes showed an almost unadjusted strategy of increased HM (6.7% (ACL); 3.9% (control), F=5.07, p=0.031) and decreased VM activation across all tasks (6.8% (ACL); 12.9% (control), F=8.52, p=0.006), whilst the control group had a clear increase in HM activation (3.2% (NORM); 5.6% (PERT), t=4.06, p=0.001) and VM activation (9.0% (NORM);16.9% (PERT), t=3.81, p=0.001) when unpredictable perturbations occurred. However, within the ACLR athletes HM activation decreased when a dual task was added (7.3% (NORM); 4.7% (DUAL), t=3.4, p=0.003). Conclusions: It seems that the neuromuscular strategy of the ACLR athlete is an overprotective strategy to improve knee stability. They use this strategy in every situation, potentially to compensate for the altered proprioceptive input. This overprotective strategy is jeopardized under cognitively challenging circumstances, confirming that underlying neurocognitive limitations contribute to altered neuromuscular control in ACLR athletes.